Geological and archaeological heritage in the Mediterranean coasts: Proposal and quantitative assessment of new geosites in SW Sardinia (Italy) - Fancello, D.; Columbu, S.; Cruciani, G.; Dulcetta, L.; Franceschelli, M. (Frontiers in Earth Science, 2022)
The south-western Sardinian coast (Italy), in the sector between the small village of Chia (Domus de Maria) and the Piscinnì locality (Teulada), is one of the most interesting of the island, being characterized by a wide geodiversity, a complex history testified by several archaeological sites, rich ecosystems, and beautiful landscapes. This area is already famous as a seaside resort, but its rich geological heritage is totally unrecognized and the educational and touristic potential of its archaeological sites is widely undervalued. In this paper, we propose an itinerary in seven stages, each of which selected considering mainly its geology (geodiversity, scientific relevance of the geological features, and educational potential), and also the additional values as the presence of archaeological sites and/or of ecological diversity and/or touristic attractions. The aim of this work is to propose the study area as a geotrail since it represents a valuable geological (and not only) heritage to be protected, preserved, and valorized in the broadest meaning of the word. The following sites have been selected: Chia tower hill, showing interesting geological features and the Punic-Roman archaeological site of Bithia; Campana and Su Giudeu beaches with their dune system and the adjacent wetlands; Settiballas, near to the Chia-Laguna resort displaying a significant geological contact; Capo Spartivento rias and cliffs; Tuerredda beach and sand dunes; Capo Malfatano, a panoramic promontory made up of 460 million years old metamorphic rocks; and Piscinnì area, where a beautiful beach and a wide Punic/Roman sandstone quarry can be observed. In addition, the most panoramic points are overlooked by Spanish towers built during the 16th to 17th century. The study area is described from geological and archaeological points of view, after a detailed field survey, the petrographic characterization of the main rocks, and an overview of the scientific literature. The quantitative assessment of the geosite values has been also performed, revealing the high potential for scientific, educational, and touristic purposes. The main concerns related to the preservation and valorization of this geosite are also addressed. Finally, a discussion on the geosite assessment methods is proposed to contribute to the scientific literature on the geoheritage. The site-by-site description is reported at the end of the paper to be used as a field guide.